2021
DOI: 10.1101/2021.12.21.21268108
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rapid rise in paediatric COVID-19 hospitalisations during the early stages of the Omicron wave, Tshwane District, South Africa

Abstract: Background South Africa reported a notable increase in COVID-19 cases from mid-November 2021 onwards, starting in Tshwane District, linked to rapid community spread of the Omicron variant. This coincided with a rapid rise in paediatric COVID-19-associated hospitalisations. Methods We synthesized data from five sources to describe the impact of Omicron on clinical manifestations and outcomes of hospitalized children (≤19 years) with positive SARS-CoV-2 tests in Tshwane District from 31 October to 11 December … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 18 publications
2
48
1
1
Order By: Relevance
“…The defective protective antibody response in patients with HM further calls for research to examine, in these patients, the possibility of enhanced strategies for immunization adjuvants to boost antibody response as well consideration of passive immune protection, using either convalescent serum, monoclonal antibodies [ 37 ] or prophylactic use of intravenous immunoglobulin (IVIG), which has recently been demonstrated to contain COVID-19 protective antibodies [ 38 ] and recently suggested as a protective strategy for immunosuppressed patients receiving CAR-T Therapy [ 39 ]. SARS-CoV-2 infections and hospitalizations are rising in the US after the emergence of the Omicron variant in December 2021 [ 40 ]. The Omicron variant is more transmissible than earlier variants.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…The defective protective antibody response in patients with HM further calls for research to examine, in these patients, the possibility of enhanced strategies for immunization adjuvants to boost antibody response as well consideration of passive immune protection, using either convalescent serum, monoclonal antibodies [ 37 ] or prophylactic use of intravenous immunoglobulin (IVIG), which has recently been demonstrated to contain COVID-19 protective antibodies [ 38 ] and recently suggested as a protective strategy for immunosuppressed patients receiving CAR-T Therapy [ 39 ]. SARS-CoV-2 infections and hospitalizations are rising in the US after the emergence of the Omicron variant in December 2021 [ 40 ]. The Omicron variant is more transmissible than earlier variants.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Pediatric SARS-CoV-2 infections and hospitalizations are rising in the US and other countries after the emergence of Omicron variant 1 . This is especially concerning for children under 5 years old since they are not eligible for COVID-19 vaccines and their low rates of previous SARS-CoV-2 infection also limits their pre-existing immunity 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous longitudinal studies have found increased SARS-CoV-2 seropositivity among children along with the overall transmission of COVID-19 [41][42][43]. In addition, with the emergence of the Omicron variant, a rise in COVID-19 pediatric cases was noted [44]. This raises the concern of the potential in uence of variants emergence on the transmission of SARS-CoV-2 among children.…”
Section: I I Resultsmentioning
confidence: 99%